Genome-Wide Association Study Reveals Marker–Trait Associations for Heat-Stress Tolerance in Sweet Corn - Quannv Yang; Zifeng Guo; Jianan Zhang; Yunbo Wang; Yunbi Xu; Hai Nian (Agronomy)
Sweet corn (Zea mays var. rugosa Bonaf.) is a crop with a high economic benefit in tropical and subtropical regions. Heat tolerance analysis and heat-tolerant gene mining are of great significance for breeding heat-resistant varieties. By combining improved genotyping using targeted sequencing (GBTS) with liquid chip (LC) technology, a high-density marker array containing 40 K multiple single polynucleotide polymorphisms (mSNPs) was used to genotype 376 sweet corn inbred lines and their heat-stress tolerance was evaluated in the spring and summer of 2019. In general, plant height, ear height and the number of lateral branches at the first level of the male flowers were reduced by 24.0%, 36.3%, and 19.8%, respectively. High temperatures in the summer accelerated the growth process of the sweet corn, shortening the days to shedding pollen by an average of 21.6% compared to the spring. A genome-wide association study (GWAS) identified 85 significant SNPs distributed on 10 chromosomes. Phenotypes in the spring and summer were associated with the 21 and 15 loci, respectively, and significant phenotypic differences between the two seasons caused by the temperature change were associated with the 49 SNP loci. The seed setting rate (SSR) was more susceptible to heat stress. An annotation analysis identified six candidate genes, which are either heat shock transcription factors (Hsfs) or heat shock proteins (Hsps) in Arabidopsis and rice (Oryza sativa), and these candidate genes were directly and indirectly involved in the heat-resistant response in the sweet corn. The current findings provide genetic resources for improving the heat-stress tolerance of sweet corn by molecular breeding.